How and When to Sign “Hey!” Socialization into Grammar in Z, a 1st Generation Family Sign Language from Mexico - John B. Haviland (Languages, 2022)
“Z” is a young sign language developing in a family whose hearing members speak Tzotzil (Mayan). Three deaf siblings, together with an intervening hearing sister and a hearing niece, formed the original cohort of signing adults. A hearing son of the original signer became the first native signer of a second generation. Z provides evidence for a classic grammaticalization chain linking a sign requesting attention (HEY1) to a pragmatic turn-initiating particle (HEY2), which signals a new utterance or change of topic. Such an emergent grammatical particle linked to the pragmatic exigencies of communication is a primordial example of emergent grammar. The chapter presents the stages in the son’s language socialization and acquisition of HEY1 and HEY2, starting at 11 months, through his subsequent bilingual development in both Z and Tzotzil, jointly deploying other communicative modalities such as gaze and touch. It proposes a series of stages leading, by 4 years of age, to his understanding of the complex sequential structure that using the sign involves. Acquiring pragmatic signs such as HEY in Z demonstrates how the grammar of a language, including an emergent sign language, is built upon the practices of a language community and the basic expected parameters of local social life.